2019
DOI: 10.1002/cl2.1048
|View full text |Cite
|
Sign up to set email alerts
|

PROTOCOL: A comprehensive review of prioritized interventions to improve the health and wellbeing of persons with lived experience of homelessness

Abstract: Worldwide, over 1.8 billion people lack adequate housing and almost 25% of the world's urban population reside in informal accommodation (United Nations Human Rights Council, 2019). "People with a lived experience of homelessness" is a term coined to describe individuals who are, have been, or at risk of becoming homeless. This population lacks stable, permanent, appropriate housing, or may be without immediate prospect, means and ability to acquire it. Such physical living situations can include emergency she… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 107 publications
0
8
0
1
Order By: Relevance
“…What is the effectiveness of income assistance on the health and social outcomes of people experiencing homelessness and those who are vulnerably housed? The protocol was registered with the Campbell Collaboration (Pottie et al, 2019) and reported according to the preferred reporting items for systematic reviews and meta-analyses for protocols (PRISMA-P; Moher et al, 2015). The results of the review are reported using the PRISMA reporting guidelines (Moher et al, 2009).…”
Section: Objectivesmentioning
confidence: 99%
“…What is the effectiveness of income assistance on the health and social outcomes of people experiencing homelessness and those who are vulnerably housed? The protocol was registered with the Campbell Collaboration (Pottie et al, 2019) and reported according to the preferred reporting items for systematic reviews and meta-analyses for protocols (PRISMA-P; Moher et al, 2015). The results of the review are reported using the PRISMA reporting guidelines (Moher et al, 2009).…”
Section: Objectivesmentioning
confidence: 99%
“…This systematic review was done in accordance with a peer-reviewed Campbell Collaboration protocol, 29 and the PRISMA 30 and SWiM 31 reporting guidelines (appendix p 5).…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%
“…We conducted a systematic review according to a published peer-reviewed protocol [29]. The protocol was not registered in an open-access registry (e.g.…”
Section: Protocol Registration and Reportingmentioning
confidence: 99%